How humans run faster: The neuromechanical contributions of functional muscle groups to running at different speeds - Willer, J.; Allen, S. J.; Burden, R. J.; Folland, J. P. (Scandinavian Journal of Medicine & Science in Sports, 2024)
How the neuromechanics of the lower limb functional muscle groups change with running speed remains to be fully elucidated, with implications for our understanding of human locomotion, conditioning, and injury prevention. This study compared the neuromechanics (ground reaction and joint kinetics, kinematics and muscle activity) of middle-distance athletes running on an instrumented treadmill at six wide-ranging speeds (2.78-8.33 m·s-1). Ground reaction forces and kinematics were analyzed using inverse dynamics to calculate flexor and extensor joint torques, and positive and negative work done by these torques. Contributions of each functional muscle group to the total positive and negative work done by the limb during stance, swing, and the whole stride were quantified. During stance, the ankle plantar flexors were the major energy generator and absorber (>60%) at all speeds, but their contribution to whole stride energy generation and absorption declined with speed. Positive work by the hip extensors rose superlinearly with speed during stance (3-fold) and especially during swing (12-fold), becoming the biggest energy generator across the whole stride at >5 m·s-1. Knee flexor and extensor negative work also rose superlinearly with speed during swing, with the knee flexors becoming the greatest energy absorber over the whole stride at >7.22 m·s-1. Across speeds, plantar flexor peak moment and positive work accounted for 97% and 96% of the variance in step length, and swing hip extension peak moment and positive work accounted for 98% and 99% of the variance in step frequency. There were pronounced speed, phase (stance/swing), and work (positive/negative) dependent contributions of the different functional muscle groups during running, with extensive implications for conditioning and injury prevention.